FRAMING PENYANDANG DISABILITAS PELAKU KRIMINAL DI MEDIA ONLINE - Wintya Nisrina Intansari; Nurul Hasfi (Interaksi Online, 2026)
News reporting on criminal offenders with disabilities potentially generates framing that violates journalistic ethical guidelines. This study aims to analyze the framing of criminal offenders with disabilities and to identify journalistic ethical violations on the online media platform Tribunnews.com. This study employs a descriptive qualitative approach utilizing Zhongdang Pan and Gerald M. Kosicki’s framing analysis method. The research subjects consist of 12 news articles concerning a criminal offender with a disability, I Wayan Agus Suartama or IWAS, published between January 9–17, 2025, on Tribunnews.com. The analysis was conducted through syntactic, script, thematic, and rhetorical structures, and evaluated using Article 8 of the Journalistic Code of Ethics and the Press Council Regulation Number 01/PERATURAN DP/II/2021 concerning Guidelines for Disability-Friendly Reporting. The results indicate that Tribunnews.com frames IWAS in four ways: as an emotional individual, having daily activity limitations, a dangerous criminal, and a vulnerable/frail party. Furthermore, all analyzed articles were identified as committing ethical violations against Article 8 of the KEJ and breaching five points (Points 1–5) of the Press Council Regulation Number 01/PERATURAN-DP/II/2021 concerning Guidelines for Disability-Friendly Reporting. Nevertheless, the reporting remains informative.